2009
DOI: 10.1002/cyto.a.20682
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy—A powerful tool for the rapid identification of microbial cells at the single‐cell level

Abstract: Rapid microbial detection and identification with a high grade of sensitivity and selectivity is a great and challenging issue in many fields, primarily in clinical diagnosis, pharmaceutical, or food processing technology. The tedious and time-consuming processes of current microbiological approaches call for faster ideally on-line identification techniques. The vibrational spectroscopic techniques IR absorption and Raman spectroscopy are noninvasive methods yielding molecular fingerprint information; thus, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
181
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(187 citation statements)
references
References 88 publications
3
181
0
3
Order By: Relevance
“…A number of studies have shown that Raman scattering-based methods allow for the assessment of the type of contamination, as well as the degree of contamination in such applications. [79][80][81][82][83][84] In early work, Choo-Smith et al 85 86 used Raman spectroscopy to quantify filtered waterborne pathogenic microbial contamination, and Pasteris et al 87 used Raman spectroscopy to identify sulfur inclusions in sulfur-oxidizing marine bacteria. Recently, Palchaudhuri et al 88 investigated the uptake and metabolism of the five-carbon sugar alcohol xylitol by gram-positive viridian group Streptococcus and two gram-negative Escherichia coli strains.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…A number of studies have shown that Raman scattering-based methods allow for the assessment of the type of contamination, as well as the degree of contamination in such applications. [79][80][81][82][83][84] In early work, Choo-Smith et al 85 86 used Raman spectroscopy to quantify filtered waterborne pathogenic microbial contamination, and Pasteris et al 87 used Raman spectroscopy to identify sulfur inclusions in sulfur-oxidizing marine bacteria. Recently, Palchaudhuri et al 88 investigated the uptake and metabolism of the five-carbon sugar alcohol xylitol by gram-positive viridian group Streptococcus and two gram-negative Escherichia coli strains.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…Bacteria were diluted to an OD of 0.1 in the particle spiked at ZnO concentrations of 5,10,20 and 50 mg/L. After 48 hours incubation, levels of total Zn and dissolved Zn were determined.…”
Section: Assessment Of Dissolutionmentioning
confidence: 99%
“…A lthough some specificity could be found, particularly in the 9 -13 cm-1 and 21 -24 cm-1 ranges, better spectral resolution is required for more certain discrimination result. We chose to characterize the E.coli DNA, which constitutes 5 -15% of an entire cell weight [41]. Fig.…”
Section: Abs Orpti On S Pectra From Different Bi Ological Speciesmentioning
confidence: 99%